The PEARL Model: Gaining Competitive Advantage Through Sustainable Development - Bilgin, Mert (Journal of business ethics, 2009)
This article formulates institutional virtues according to sustainable development (SD) criteria to come up with a paradigmatic set of corporate principles. It aims to answer how a corporation might obtain competitive advantage by combining “going ethical” with “going green.” On the one hand, it brings out facts that indicate a forthcoming trend inclined to force relevant actors to comply with SD requirements. On the other hand, it suggests that SD may be implemented as a strategy to gain competitive advantage by the help of the PEARL model through its five fundaments: (1) perception friendliness, (2) environment friendliness, (3) action, (4) relationship, and (5) locality. This article finally shows that although a number of companies (e.g., Bosch, BP, and GE) implement SD as a tool of differentiation, they lack a holistic model that is fully responsive to current dynamics. The PEARL may be implemented as a proactive positioning to gain competitive advantage because transformation of this model into corporate strategy does not only respond to “stakeholder” claims, but also meets the changing characteristic of “societal demands.”